Implementasi manajemen pendidikan karakter dalam pembelajaran Ilmu Pengetahuan Sosial - Mahbubah, Sahiyatul (Maliki Interdisciplinary Journal, 2024)
In every study, both in formal and non-formal education, it must be based on existing national education goals. Education has the goal of developing the potential of students to become people of faith and piety, character, noble character, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible state. However, education in Indonesia currently has not fully answered this problem. In other words, education in Indonesia has not been able to fully form a young generation that is superior and has character. The superiority of the younger generation can be formed through a series of efforts to increase student achievement, while student character can be formed through moral example obtained in character education. Through character education it is hoped that positive transformation will occur which can grow, develop and change bad character to be good. From here the presence of social studies learning as a vehicle for achieving national education goals and character education. The writing method was carried out by means of a literature review (literary study). The character education strategy in social studies learning includes the planning stage of developing character sets, which includes writing syllabuses, lesson plans, (adding or modifying the development of character values), preparing teaching materials (adding learning activities with character education from a process standpoint), and learning media (for example the teacher develops used goods, students will develop creativity and love for the environment). Teachers can use fun active learning strategies when carrying out learning, including active learning through the team building method. This approach is to instill character values ​​such as cooperation, caring, friendliness, peace-loving, communication, democracy, and tolerance. At the results assessment stage, well-designed measurements (assessments) and continuous improvement are carried out to determine student character achievements. The selected and implemented assessment techniques and devices do not only measure knowledge or cognitive attainment, but also measure students' attitudes and personalities. The assessment techniques can be carried out by means of written tests, oral tests, performance tests, individual/group assignments, observation, portfolio assessment, observation sheets, self-assessment (with evaluation sheets/questionnaires) and assessments between classmates.